1989
DOI: 10.1152/jappl.1989.66.3.1143
|View full text |Cite
|
Sign up to set email alerts
|

Muscle plasticity: comparison of a 30-Hz burst with 10-Hz continuous stimulation

Abstract: The changes in the contractile properties induced by a 30-Hz phasic stimulation paradigm were measured and compared with the changes induced by a 10-Hz continuous stimulation paradigm. The study was performed on the tibialis anterior muscles of cats with one paradigm applied to one hindlimb muscle and the other to the contralateral limb. Both hindlimb muscles received the same number of stimuli in a day, making the average stimulation frequency 10 Hz. Two periods of daily stimulation were studied, 8 and 24 h/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 0 publications
5
26
0
Order By: Relevance
“…6,[12][13][14]28 In the context of chronic stimulation, muscle mass and tetanic tension are preserved to a greater extent in innervated muscles subjected to bursts containing a highfrequency component. 9,10,18,32 In the present study, as in the related clinical studies, the primary aim was the restoration of muscle bulk, and frequencies were therefore chosen that were as high as possible, consistent with the long pulse durations needed to excite the fibers.…”
Section: Discussionmentioning
confidence: 99%
“…6,[12][13][14]28 In the context of chronic stimulation, muscle mass and tetanic tension are preserved to a greater extent in innervated muscles subjected to bursts containing a highfrequency component. 9,10,18,32 In the present study, as in the related clinical studies, the primary aim was the restoration of muscle bulk, and frequencies were therefore chosen that were as high as possible, consistent with the long pulse durations needed to excite the fibers.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, previous workers have shown isoform switching using chronic stimulation over several weeks or months [7,28]. Our model differs in that protein synthesis is activated by stretch combined with electrical stimulation causing the muscle rapidly to produce new actin and myosin filaments in series and in parallel "201.…”
mentioning
confidence: 97%
“…However, more recently, it was shown that stimulation with 30 Hz [28] or 60 Hz intermittent stimulation [29] was more effective in transforming fast into slow muscles than the continuous stimulation with 10 Hz used by previous workers.…”
mentioning
confidence: 99%
“…Stimulus bursts containing a high-frequency component are the most effective for maintaining the mass and forcegenerating capacity of the muscle [51,[55][56][57]. Instead of conventional constant, high-frequency bursts, it is more physiological to use bursts in which the interpulse intervals are optimised for maximum force [58].…”
Section: Stimulation With Optimised Burstsmentioning
confidence: 99%